The Metaphors of Rain in Lithuanian and Russian Poetry - Konickaja, Jelena; Jasiūnaitė, Birutė (Vilnius University Open Series, 2020)
The current article, which is one of the further researches on the metaphors of natural phenomena in Lithuanian and Russian poetry, discusses the metaphors of rain (based on the works of 45 Lithuanian and 57 Russian poets). They reflect the following aspects of the phenomenon: acoustic, dynamic, temporal, visual, temperature, as well as its intensity, destructive consequences, belonging to a certain season and others. The metaphorical expressions are divided into seven semantic groups: 1) anthropomorphic, 2) zoomorphic, 3) biomorphic (plant), 4) associated with inanimate nature objects and phenomena, 5) ‘material’ (subject), 6) related to abstract concepts, and 7) others. In both languages, the anthropomorphic and subject groups of metaphors have turned out to be the largest, while the smallest groups are zoomorphic, biomorphic (plant) and abstract metaphors. The comparison of the metaphorical expressions that define rain in Lithuanian and Russian poetry showed that there are common metaphorical models, however, there are also differences that are related to the prevalence of certain models, as well as their presence/absence in one of the two languages. Thus, among zoomorphic metaphors, the models rain-bird (with a common wing image), rain-horse and rain-small creature are common, while their difference consists in the fact that the models are used to characterize various properties of rain. For instance, a popular Lithuanian verb metaphor the rain blooms, as well as the comparison of rain with flowers (a biomorphic (plant) group of metaphors), are absent in Russian poetry. The richness and diversity of rain metaphors in Lithuanian and Russian poetry illustrate the authors’ ability to use a number of images that have already existed in the language and their creativity to utilize absolutely new comparisons that are usually fit for the existing metaphorical models.